DLTS Study of InGaAsN/GaAs p-i-n Diode - Jakub Rybar; Lubica Stuchlikova; Ladislav Harmatha; Juraj Jakus; Jaroslav Kovac; Beata Sciana; Damian Radziewicz; Damian Pucicki; Wojciech Dawidowski; Marek Tlaczala (Communications - Scientific letters of the University of Zilina, 2014)
The paper presents an in-depth DLTS characterization of the p-i-n structure based on the InGaAsN/GaAs triple quantum well. Three DLTS evaluation methods were used for evaluation of the measured DLTS spectra. The results of all evaluation methods are compared and discussed. One of the evaluation methods that were used is a novel numerical algorithm that was recently developed. Several material and growth defects were identified. Emission from the quantum well was also observed and identified. The parameters of the energy levels were calculated and compared. The studied InGaAsN/GaAs structure is promising candidate for the solar cell applications and the further refinement of the growth process and technology is encouraged.